2013
DOI: 10.1161/circulationaha.113.003139
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-Like Progenitor Cells Engineered to Produce Prostacyclin Rescue Monocrotaline-Induced Pulmonary Arterial Hypertension and Provide Right Ventricle Benefits

Abstract: P ulmonary arterial hypertension (PAH) is a progressive disorder characterized by abnormally high blood pressure in the pulmonary artery, right ventricular (RV) overload, and, eventually, right heart failure leading to death. The estimated median survival of patients diagnosed with idiopathic PAH is <3 years. 1 The only treatment option that has been shown to increase the survival rate is the continuous systemic administration of prostacyclin 2 ; the median survival rate increases from 2.8 years in untreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 47 publications
(53 reference statements)
0
27
0
Order By: Relevance
“…Another study demonstrated that altered CYP levels contributed to vascular and tubular abnormalities in renal disease [22]. Accumulating evidence suggests that the expression of enzymes involved in AA metabolism is related to the progression of many diseases, such as pulmonary artery hypertension and inflammation [23,24]. Given that balanced levels of AA metabolites regulate cell function and disease condition, changes in the level of specific AA metabolites may reflect systematic responses to stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that altered CYP levels contributed to vascular and tubular abnormalities in renal disease [22]. Accumulating evidence suggests that the expression of enzymes involved in AA metabolism is related to the progression of many diseases, such as pulmonary artery hypertension and inflammation [23,24]. Given that balanced levels of AA metabolites regulate cell function and disease condition, changes in the level of specific AA metabolites may reflect systematic responses to stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…autologous or heterologous transplantation), 5) age of cells, and most importantly, 6) targeting delivery of cells to damaged organs to maximize therapeutic effects. Several strategies including growth factor delivery (15,17), gene therapy (14,18,19) and stem cell therapy (16,17) have been developed to promote vascular repair in pulmonary vascular diseases. Among them, cell-based therapy has emerged as the most promising therapeutic tool for treatment of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Both non-selective bone marrow-derived stem cells (MSCs) and selective endothelial progenitor cells (EPCs) have been used in rodent models of hypoxia- or MCT-induced pulmonary arterial remodeling and hypertension (11,1417). Intra-tracheal administration of MSCs has been shown to attenuate neonatal hyperoxia-induced lung injury (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of delivery, and the adverse effect profile of the currently available PAH-specific drugs create further management difficulties. Nanoparticle-mediated drug delivery systems, including solid lipid nanoparticles, polymeric nanoparticles and liposomes [65,66], along with the use of stem cells/ progenitor cells as a vehicle for endothelial vasodilatory agents, such as prostacyclin-producing cells [67], are currently under investigation. These will open new perspectives in PAH treatment by modifying the problematic physical properties of currently available drugs, for example increasing drug solubility, encapsulation efficacy and surface changes to improve drug release and maximizing the effect.…”
Section: Future Researchmentioning
confidence: 99%